The Role of Management Accounting in Enhancing Business Agility and Decision- Making - Agarwal, Dr. Varsha; Ghosh , Dr. ParthaPratim; Momin , Dr. UzmaTanveer; Nagappan , Beemkumar; Madan , Praney; Faiz , Ayaan; Asthana , Dr. Sapan (International Journal of Accounting and Economics Studies, 2025)
The modern business environment is constantly challenging and evolving at a tremendous pace and intense international competition has forced business organizations to increase the speed, quality, performance and decrease cost. All these demand timely and effective decision-making, which creates need of decision support systems and technologies. Accounting information is applied in all stages of management, such as planning, controlling, and decision making. In addition, such information is not only required by manufacturing organizations but also employed in manufacturing, merchandising, service, and nonprofit organizations. Accounting is business language. "It can employ this language to convey financial transactions and their consequences. Accounting is complete systems to gather, analyze, and convey financial data. The history of accounting is as old as money.". In initial days, the volume of transactions was small, and thus each concerned person could maintain the record of transactions for a limited span of time. Management accounting facilitates the recording and analyzing of financial information which can be employed by a firm to make itself more efficient and productive. By using simple techniques such as standard costing, marginal costing, project evaluation, and control accounting, it consistently provides financial data. However, financial statements are the sole source of information needed for making managerial decisions. Therefore, it’s crucial to ensure that records are error-free. Despite some drawbacks, this approach proves to be a valuable tool for effective business management.